Bis(trimethylphenylammonium) tetrabromidocuprate(II) - Lo, K.M.; Ng, S.W. (International Union of Crystallography, 2010)
The crystal structure of the title compound, (C(9)H(14)N)(2)-[CuBr(4)], consists of two quarternary ammonium cations and a tetrahedral cuprate anions. Weak C-H center dot center dot center dot Br hydrogen bonding is present between the cation and anion in the crystal structure.